Identification of reflection, diffraction and scattering effects in real acoustic flow fields - Weyna, S. (Archives of Acoustics, 2003)
In contrast to the classically described acoustical fields with acoustical pressure distributions (scalar effects), the graphical presentation of the acoustic energy flow in real-life acoustic fields as a vector mapping, can explain many particulars concerning the areas in which it is difficult to make a theoretical analysis (direct and near field, vortex flow, effects of scattering on obstacles, reflection on partitions, efficiency of acoustics barrier, etc.). With the experimental application of the sound intensity (SI) measurement method in real-life fields as well as the technique of presentation the results in a 2D and a 3D graphical form, numerous examples illustrate the results of applying the SI measurement for practical problems presented in the article. Concerning the intensity vector distribution of the real near and fare field, the paper presents the paths of the acoustic energy flow over the barriers and the form of the acoustical radiation field of vibrating structures. This type of information enriches the knowledge about vector acoustic fields and the mechanism of the acoustic energy flux through the real partitions.